Paradygmat romantyczny w dyskursie publicznym na przykładzie zbioru wywiadów "Smoleńsk" Teresy Torańskiej = Romantic paradigm in public discourse on the example of the book "Smoleńsk" by Teresa Torańska - Rostkowska-Biszczanik, Kaja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
References to the set of heroic and romantic values, characteristic of the first half of the nineteenth century, had another culmination in Poland in the twentieth century. The rebirth of the romantic paradigm occurred also after the presidential plane crash in 2010. The public post-Smoleńsk discourse, multithreaded, extended between politics, religion and science, should be completed with a reflection from the border between media and literature, possible thanks to, among others, the groundbreaking book "Smoleńsk" by Teresa Torańska, presenting the events from many perspectives.
Keywords: dyskurs publiczny; paradygmat; romantyzm; wywiad; Smoleńsk; public discourse; paradigm; romanticism; interview